The Concept of Islamization of Knowledge in the Thought of Syed Muhammad Naquib Al-Attas: An Effort to Build a True Islamic Epistemology - Nasution, Anjar Mahmudin; Helmiati, Helmiati; M., Nazir; Lubis, Ardiansyah (Al Ulya: Jurnal Pendidikan Islam, 2026)
This article aims to examine the conceptual construction of the true Islamic paradigm according to Syed Muhammad Naquib al-Attas and evaluate its relevance and contribution to the development of contemporary Islamic epistemology and education systems. This study uses the Systematic Literature Review (SLR) method by analyzing 24 scientific articles selected from 100 Scopus journal publications published between 2015 and 2025. The selection process was based on inclusion criteria that included the type of scientific journal article, direct relevance to the concept of Islamization of knowledge according to al-Attas, open access, and the most recent publication period to ensure the relevance and credibility of the sources. The results of the study show that the true Islamic paradigm constructed by al-Attas is based on the worldview of tawhid, placing adab as the epistemological basis, and positioning science as an instrument for self-knowledge, knowledge of God, and knowledge of reality. This paradigm rejects epistemological secularism and the dichotomy of science, and integrates the dimensions of revelation, reason, intuition, and experience into a holistic Islamic scientific framework. The uniqueness of this study lies in its affirmation of the integral relationship between adab and the structure of knowledge as the foundation of the Islamization of science, which has not been systematically elaborated in previous studies. This paradigm makes a significant contribution to strengthening Islamic epistemology that has spiritual value as well as reforming the education system through the concepts of ta'dib, the hierarchy of knowledge, and the integration of a curriculum based on maqasid al-shari'ah. Thus, the true Islamic paradigm is not only the theoretical basis for the Islamization of science, but also a strategic offer in the reconstruction of an integral and civilized Islamic education system.